Kinematic profile of the elite handcyclist - Abel, T.; Bonin, D.; Albracht, K.; Zeller, S.; Brüggemann, G.; Burkett, B.; Strüder, H. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
A handcycle is a relatively new sports equipment that is a combination of the traditional race wheelchair and a hand operated bicycle crank (Abel, Schneider, Platen, & Struder, 2006). The high mechanical efficiency of this geared fixed-frame racing cycle in comparison to a manual wheelchair can potentially increase the distance a person with a loss of lower limb function can travel. To guide the optimal setup for the handcyclist the influence of crank length (Goosey-Tolfrey, Alfano, & Fowler, 2008; Kramer, Hilker, & Bohm, 2009) and crank configuration (Faupin, Gorce, Meyer, & Thevenon, 2008a; Mossberg, Willman, Topor, Crook, & Patak, 1999) have been investigated. Actual neither research has been done on the upper body kinematics of elite athletes nor on relations between kinematics and performance. The aim of this study was to provide first sport specific information in this area with regards to athletes competing at an international level.